A mixed-methods study measuring the effectiveness of a menstrual health intervention on menstrual health knowledge, perceptions and practices among young women in Zimbabwe. Issue 3 (9th March 2023) - Tembo, Mandikudza; Weiss, Helen A; Larsson, Leyla Sophie; Bandason, Tsitsi; Redzo, Nicol; Dauya, Ethel; Nzanza, Tafadzwa; Ishumael, Pauline; Gweshe, Nancy; Ndlovu, Precious; Dziva Chikwari, Chido; Mavodza, Constancia Vimbayi; et al.
Abstract : Objectives: While integral to women's physical and mental well-being, achieving good menstrual health (MH) remains a challenge for many women. This study investigated the effectiveness of a comprehensive MH intervention on menstrual knowledge, perceptions and practices among women aged 16–24 years in Harare, Zimbabwe. Design: A mixed-methods prospective cohort study with pre-post evaluation of an MH intervention. Setting: Two intervention clusters in Harare, Zimbabwe. Participants: Overall, 303 female participants were recruited, of whom 189 (62.4%) were seen at midline (median follow-up 7.0; IQR 5.8–7.7 months) and 184 (60.7%) were seen at endline (median follow-up 12.4; IQR 11.9–13.8 months). Cohort follow-up was greatly affected by COVID-19 pandemic and associated restrictions. Intervention: The MH intervention provided MH education and support, analgesics, and a choice of menstrual products in a community-based setting to improve MH outcomes among young women in Zimbabwe. Primary and secondary outcomes: Effectiveness of a comprehensive MH intervention on improving MH knowledge, perceptions, and practices among young women over time. Quantitative questionnaire data were collected at baseline, midline, and endline. At endline, thematic analysis of four focus group discussions was used to further explore participants' menstrual product use and experiences of the intervention. Results: At midline, more participants had correct/positive responses for MH knowledge (adjusted OR (aOR)=12.14; 95% CI: 6.8 to 21.8), perceptions (aOR=2.85; 95% CI: 1.6 to 5.1) and practices for reusable pads (aOR=4.68; 95% CI: 2.3 to 9.6) than at baseline. Results were similar comparing endline with baseline for all MH outcomes. Qualitative findings showed that sociocultural norms, stigma and taboos around menstruation, and environmental factors such as limited access to water, sanitation and hygiene facilities affected the effect of the intervention on MH outcomes. Conclusions: The intervention improved MH knowledge, perceptions and practices among young women in Zimbabwe, and the comprehensive nature of the intervention was key to this. MH interventions should address interpersonal, environmental and societal factors. Trial registration number: NCT03719521 .